The Thorneycroft Patent Rifle. (3rd July 2019) - Ferguson, Jonathan
Abstract : The latter part of the 20 th century saw widespread military adoption of rifles in a shortened configuration known as 'bullpup', with the working parts located behind the trigger. This was directly informed by developmental work carried out during and following the Second World War. However, arguably the first cogent effort was the 'Thorneycroft Patent Rifle', a design first conceived in 1901 and subjected to three main iterations as well as British military trials. At the time of writing, little has appeared in print about either the Thorneycroft rifle or its designers. This article seeks to comprehensively document this interesting type using available sources and analysis of surviving rifles as both historical artefacts and pieces of engineering. It also places the rifle in the context of the developmental history of the 'bullpup' configuration.